2019
DOI: 10.1038/s41591-019-0462-y
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning can predict microsatellite instability directly from histology in gastrointestinal cancer

Abstract: This is a repository copy of Deep learning can predict microsatellite instability directly from histology in gastrointestinal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
886
5
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 987 publications
(922 citation statements)
references
References 25 publications
19
886
5
12
Order By: Relevance
“…There is, therefore, a great need to screen standard WSIs from patients with solid tumors with a high probability of MSI-H directly, to facilitate access to immunotherapy. A recent study 54 showed that CNNs can learn to predict MSI status directly from histology slides for stomach adenocarcinoma and colorectal cancer. Based on these results, we collected, from the TCGA-COAD dataset, RNA-Seq measurements, WSIs and the corresponding MSI status of each patient from the dataset, to investigate the effects of integrating RNA-Seq information on the prediction of MSI status from pathology images.…”
Section: A Deep Learning Model For the Prediction Of Gene Expressionmentioning
confidence: 99%
“…There is, therefore, a great need to screen standard WSIs from patients with solid tumors with a high probability of MSI-H directly, to facilitate access to immunotherapy. A recent study 54 showed that CNNs can learn to predict MSI status directly from histology slides for stomach adenocarcinoma and colorectal cancer. Based on these results, we collected, from the TCGA-COAD dataset, RNA-Seq measurements, WSIs and the corresponding MSI status of each patient from the dataset, to investigate the effects of integrating RNA-Seq information on the prediction of MSI status from pathology images.…”
Section: A Deep Learning Model For the Prediction Of Gene Expressionmentioning
confidence: 99%
“…As a tool for feature extraction from images, we used deep learning, a form of artificial intelligence (AI), which has previously been used to detect high-level morphological features directly from histological images. 8-10…”
Section: Introductionmentioning
confidence: 99%
“…In domains like computer vision or natural language processing, deep neural networks have already dramatically improved state-of-the-art prediction performances (Goodfellow et al 2016;LeCun et al 2015). However, in the application of neuroimaging data analysis, a similar revolution has not materialized for most common prediction goals, despite considerable research effort and few successful exceptions, such as for the goal of image segmentation (Choi & Jin 2016;Kamnitsas et al 2017;Li et al 2018;Kather et al 2019) and image registration (Balakrishnan et al 2018;Yang et al 2017).…”
Section: Deep Learning Did Not Universally Improve Prediction Performmentioning
confidence: 99%